Introduction: The Liberal Script at the Beginning of the 21st Century - Tanja A. Börzel; Johannes Gerschewski; Michael Zürn (The Liberal Script at the Beginning of the 21st Century: Conceptions, Components, and Tensions, 2024)
This chapter discusses the added value of using “script” as a heuristic and an analytical concept over alternatives and introduces four central themes that structure this volume. We ask first what the liberal script is and how we can approach it from different viewpoints. Second, we inquire how the liberal script varies over time and space. Third, we distinguish subscripts and major components of the liberal script. Fourth, we identify tensions emerging within the liberal script and possible resolutions. In each section, we introduce individual contributions to the book and show how they deal with the four central themes.
Keywords: 300; liberal script; contestations; liberal international order; illiberalism; liberalism